Pengaruh Kepemimpinan, Motivasi dan Disiplin Kerja terhadap Kinerja Pegawai di Puskesmas - Maria Anita Atu Wea; M. Syamsu Hidayat; Rochana Rulyandari (LPPM Institut Pendidikan Nusantara Global, 2025)
Employee performance at Puskesmas is a crucial factor in achieving effective and sustainable primary health care services; however, it is strongly influenced by leadership, motivation, and work discipline that develop within the socio-cultural context of public organizations. This study aims to examine in depth the relationship between these three factors and employee performance at Puskesmas through a qualitative literature review approach. The data were obtained from a systematic review of relevant national and international scientific journal articles, and the analysis was conducted using a thematic method to identify patterns, concepts, and interrelationships among factors affecting employee performance. The results indicate that transformational and participatory leadership plays a dominant role in enhancing employee motivation and strengthening work discipline, as leaders who provide vision, inspiration, and active involvement are able to encourage employees to perform optimally. Intrinsic motivation rooted in public service values is proven to be essential in maintaining dedication, commitment, and professional responsibility, while work discipline is understood not merely as procedural compliance, but also as a reflection of moral values and professional ethics. The interaction of leadership, motivation, and work discipline forms a strong work commitment that positively impacts service quality, efficiency, and responsiveness in primary health care delivery, thereby reinforcing the role of Puskesmas as the frontline of public health services.